Tinjauan Konseptual Mikro-Makro Daya Saing dan Strategi Pembangunan Pertanian - nFN Saptana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2010)
EnglishPolicy makers and economists are interested in competitiveness concept and try to implement in the economic development. Competitiveness has several perspectives, i.e. economic perspective, business, and politic. Competitivess could also be reviewed in a micro perspective (company level) and macro perspective (national level). This paper examines the competitiveness concept in terms of micro and macro perspectives. The micro perspective would be useful in agricultural development, especially in crop selection and in endeavor to change comparative to competitive advantages. The macro perspective should be useful to improve national competitiveness trough various fiscal policies of real sector. The study revealed that several agricultural commodities have competitive and comparative advantages, but the competitiveness susceptible to external fluctuation. The changes from comparative to competitive advantage require government intervention to control market distortion and to reduce the high transaction cost economy. Meanwhile, the changes from competitiveness at company level to competitiveness at national level need an integrated macro economic policies and micro economic activities. IndonesianPakar ekonomi dan pengambil kebijakan telah memberikan perhatian besar terhadap konsep daya saing dan mencoba mengoperasionalkan dalam pembangunan ekonomi. Konsep daya saing dimaknai dari berbagai perspektif, antara lain perspektif ekonomi, bisnis, dan politik (kebijakan). Di samping itu, ada yang memaknai dalam perspektif mikro (perusahaan) dan perspektif makro (nasional). Tulisan ini berusaha mengkaji konsep daya saing dalam perspektif ekonomi baik mikro maupun makro. Kajian dari perspektif mikro diharapkan berguna dalam pembangunan pertanian terutama untuk menentukan pilihan komoditas dan upaya mewujudkan keunggulan komperatif menjadi keunggulan kompetitif. Sementara itu, dari kajian dalam perspektif makro diharapkan berguna membangun daya saing nasional melalui berbagai kebijakan makro terutama melalui kebijakan fiskal di sektor riil. Secara mikro beberapa komoditas pertanian Indonesia mempunyai keunggulan komparatif dan kompetitif, namun keunggulan yang dimiliki rentan terhadap gejolak eksternal. Untuk mewujudkan keunggulan komparatif menjadi keunggulan kompetitif diperlukan adanya kebijakan pemerintah yang ditujukan untuk menghilangkan adanya distorsi pasar dan menekan tingginya biaya transaksi. Sementara itu, untuk mewujudkan daya saing di tingkat mikro (perusahaan) menjadi daya saing di tingkat makro (nasional) diperlukan adanya keterpaduan antara kebijakan makro dan kegiatan ekonomi mikro.